Switchable magnetic dipole assisted double QBICs in an asymmetry four-leaf clover-shaped Ge₂Sb₂Te₅ metasurface - Zhou, Rujun (2023)
Dynamically tunable metasurface resonators with high Q factors and excellent sensing performance still lack research. This paper proposes a dual-band symmetry broken induced quasi bound state in the continuum (QBIC) sensor in the near-infrared region based on an asymmetric four-leaf clover-shaped Ge2Sb2Te5 (GST) metasurface. The high-quality transmission spectrum can be tuned by switching the GST crystalline state. Two QBIC magnetic dipole resonances are excited at the amorphous GST state, QBIC Ⅰ (intracavity MD mode) and QBIC Ⅱ (intercavity high-order MD mode). Based on theoretical simulation, the refractive index sensitivity of the QBIC Ⅱ mode (318.05 nm/RIU) is enhanced higher than twice of the QBIC Ⅰ mode (134.03 nm/RIU) owing to the unique electromagnetic field properties. The ultra-high Q factors generated by the two MD resonance modes are 1.1 × 105 (QBIC Ⅰ) and 1.71 × 105 (QBIC Ⅱ) respectively for a small perturbation of the air hole offset distance D = 5 nm. By discussing the effect of the main structure parameters and the analyte thickness on the sensitivity, the optimal parameters are determined. The two strong QBICs supported by the a-GST metasurface are stable when the air hole's offset from the unit center is at different directions and distances, indicating a good tolerance to fabrication requirements. These results provide a competitive switchable dual-band QBIC metasurface sensor, providing a potential route for tunable metadevices for functional sensing and dynamic control over signals.